Coho salmon Oncorhynchus kisutch (Walbaum) on the continental coast of the Okhotsk Sea - S. L. Marchenko (Известия ТИНРО)
Coho salmon is a common object of ichthyofauna in the water bodies of the continental coast of the Okhotsk Sea, with the main stocks concentrated in the central part of the region. The species exhibits mostly the anadromous life strategy in the ontogenesis, though the resident groups are known in three lakes located in the basins of Inya, Ul’beya and Okhota Rivers. Temporal structure of anadromous coho salmon is demonstrated for the first time within the region: the stock is presented by two forms, as early and late ones. Spawning runs of these forms could be indicated by changes of qualitative parameters of fish. Coho salmon of the early and late forms reproduce on spawning grounds with different hydrological and thermal regimes. Juvenile coho salmon spend from 1 to 3 years in the fresh water before the seaward migration. Duration of marine period of their life is usually 1 year, but rarely they return for spawning either in the year of seaward migration or after two winters in the sea. Variability of abundance and qualitative parameters of coho salmon is conditioned mainly by environments of reproduction and feeding, with some impact of epigenetic difference in size and age between the life strategies in ontogenesis.